2016
DOI: 10.4338/aci-2015-11-ra-0160
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Home Care Clinicians’ Information Needs for Managing Fall Risks

Abstract: KeywordsHome health agencies, health information technology, quality of care, workflow, information management SummaryObjectives: To help manage the risk of falls in home care, this study aimed to (i) identify home care clinicians' information needs and how they manage missing or inaccurate data, (ii) identify problems that impact effectiveness and efficiency associated with retaining, exchanging, or processing information about fall risks in existing workflows and currently adopted health information technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Health information technology provides hope to facilitate the timely and efficient collection and transmission of patient information across care settings to support care decisions. The value of health information technology on care planning and care provision in HH was recently established (Alhuwail & Koru, 2016; Sockolow, Bass, Eberle, & Bowles, 2016; Sockolow, Bowles, Adelsberger, Chittams, & Liao, 2014). One potential strategy is to promote the use of a standardized document such as the Continuity of Care Document within electronic medical documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Health information technology provides hope to facilitate the timely and efficient collection and transmission of patient information across care settings to support care decisions. The value of health information technology on care planning and care provision in HH was recently established (Alhuwail & Koru, 2016; Sockolow, Bass, Eberle, & Bowles, 2016; Sockolow, Bowles, Adelsberger, Chittams, & Liao, 2014). One potential strategy is to promote the use of a standardized document such as the Continuity of Care Document within electronic medical documentation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 HHCAHPS results reported that 16% of patients said that their home care team did not discuss their medications, pain, or home safety with them ( 53 ). To improve the experience of patients and caregivers in fall-risk management and score higher on HHCAHPS surveys, HHAs could adopt solutions such as patient portals that could help them improve the communication and reinforce the education of patients and caregivers about fall risks and home safety ( 54 , 55 ), investigate providing the patients and caregivers access to the clinical notes in the electronic health record ( 56 ), and examine care coordination problems and enhance information sharing with hospitals and physicians by leveraging health information exchange solutions ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Saari et al 15 identified technology as having the ability to facilitate effective communication and address information gaps for health care aides. Consequently, opportunities for ICT intended for health care aides include features of portability, 44 ubiquity, 45 interoperability, 46 communication tools to assist care plans, 43 and integration with remote care, telemonitoring, and assistive technologies. 36 To our knowledge, no comprehensive review has studied the range and extent of ICT used by health care aides to support their workflows and practice.…”
Section: Background and Significancementioning
confidence: 99%
“…We classified the selected studies in five groups, according to the main purpose of ICT use by health care aides: (1) improve everyday work (n ¼ 12, 30%), 46,[51][52][53][54][55][56][57][58][59][60][61] (2) access electronic health records for home care (n ¼ 9, 22.5%), [62][63][64][65][66][67][68][69][70] (3) facilitate client assessment and care planning (n ¼ 9, 22.5%), [71][72][73][74][75][76][77][78][79] (4) enhance communication (n ¼ 7, 17.5%), 2,40,80-83 and (5) provide care remotely (n ¼ 3, 7.5%). 35,84,85 Fig.…”
Section: Study Purposementioning
confidence: 99%